Beta-blockers in elderly patients with left ventricular systolic dysfunction and chronic kidney disease: danger or benefit?. (25th November 2020) - Martinez Milla, J; Cortes, M; Lopez-Castillo, M; Devesa-Arbiol, A; Rivero-Monteagudo, A.L; Taibo, M; Martin-Mariscal, M.L; Briongos, S; Franco-Pelaez, J.A; Tunon, J
Abstract: Introduction: Beta-blockers (BB) have been shown to reduce mortality in patients with HFrEF. However, there is little data on the benefit of these therapies in patients with chronic kidney disease and even less in older patients. The aim of this work is to evaluate the role of beta-blockers in patients ≥75 years along the spectrum of kidney disease. Methods: From January 2008 to July 2014, we consecutively enlisted 802 patients aged >75 years that had ejection fraction ≤35%. From this group we included 380 patients that had CKD (defined as a glomerular filtration rate (GFR) ≤60 ml/min/1.73m 2 ). Clinical, echocardiographic and electrocardiographic data were taken from hospital records. Follow-up was made via telephone and hospital records as well. Propensity score matching analysis was made to assess the relationship between treatment with BB and occurrence of major adverse cardiovascular event (MACE) composite of death for any cause or heart failure. hospitalization. Multivariate Cox regression analysis was also made in the different groups of CKD (45–60 ml/min/1.73m 2, 30–45 ml/min/1.73m 2, <30 ml/min/1.73m 2 ) in order to assess the effect of BB over mortality and CV events in each subgroup. Results: 390 patients were included. Male represented 62.3% of all participants, and the mean age was 82.6±4.1 years. The mean ejection fraction was 27.9±6.5%. Ischemic etiology was found in 50.6% of cases. Glomerular filtrate (GF) was 60 to 45 ml/min/1.73 m 2 in 50.3% of patients, 45–30 ml/min/1.73 m 2 in 37.4% and <30 ml/min/1.73 m 2 in 12.3%. At the end of the follow-up, 67.4% of the patients were on beta-blocker treatment. The mean follow-up was 32±23 months. During the study period, 211 patients (54.1%) died and 257 patients (65.9%) had a major cardiovascular event (death or hospitalization for heart failure). After propensity score matching analysis, 178 were considered (89 each group) and they have no significant difference in baseline characteristics. BBs were found to significantly reduce mortality (HR 0.45 (95% CI, 0.27–0.75). When the effect of BB over the different subgroups of CKD was analyzed, it was seen also that BB reduced mortality in patients with eGFR 45–60 ml/min/1.73 m 2 (HR 0.47 (95% CI, 0.26–0.86), in patients with eGFR 30–45 ml/min/1.73 m 2 (HR 0.55 (95% CI, 0.26–1.06)and in eGFR <30 ml/min/1.73 m 2 (HR 0.29 (95% CI, 0.11–0.76) Conclusion: The use of beta-blockers in elderly patients with HFrEF and kidney DISEASE was associated with increased survival, regardless of the degree of kidney failure. There is a need to raise awareness of the benefits of beta-blocker use in these patients to promote their use where possible. Funding Acknowledgement: Type of funding source: None